Fluorocarbonate nonlinear optical crystal and growth method

By using hydrothermal method to grow potassium fluorocarbonate (K4Tb2(CO3)3F4) single crystals under high temperature and high pressure conditions, the problem of difficult preparation of fluorocarbonate crystals in the prior art is solved, and high quality is achieved Nonlinear optical properties and larger crystal sizes are suitable for optoelectronics and optical communications fields.

CN118256995BActive Publication Date: 2024-12-13GUILIN BAILUI PHOTOELECTRIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311790636.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2024-12-13
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nonlinear optical crystals of fluorocarbonate with high purity and low thermal stress, especially transition metal carbonates, with low decomposition temperature, making it difficult to find suitable cosolvents, resulting in insufficient preparation efficiency and quality of the crystals.

Method used

Potassium terbium fluorocarbonate (K4Tb2(CO3)3F4) single crystal was grown by hydrothermal method, and the temperature was controlled by using high-temperature and high-pressure conditions (500-650℃) and subcritical water in the autoclave, combined with gold bushing and resistance furnace. Slowly drop to room temperature, reduce macroscopic defects and thermal stress, and improve the crystallization quality of the crystal.

Benefits of technology

A fluorocarbonate nonlinear optical crystal with high purity and low optical loss has been obtained, with better transparency and frequency doubling effects, and is suitable for the fields of optoelectronics and optical communications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118256995B_ABST
    Figure CN118256995B_ABST
Patent Text Reader

Abstract

The invention discloses a fluorocarbonate nonlinear optical crystal and a growth method thereof, wherein the chemical formula is K 4 Tb 2 (CO 3 ) 3 F 4 , belongs to the trigonal system, the space group is R32, and the unit cell parameters are #imgabs0#α=β=90.0000°, γ=120.0000°; #imgabs1# The crystal is grown by subcritical hydrothermal method. Carbonate is easy to decompose at high temperature. The temperature used in the present invention is a high temperature and high pressure hydrothermal method above 500°C. The growth temperature is lower than that of the molten salt method. The obtained crystal has high purity, small thermal stress, few macro defects, better crystal quality and larger crystal size. The crystal of the present invention is a new type of rare earth terbium material coordinated by fluorine and carbonate, which has good nonlinear optical properties, can achieve higher transparency and lower optical loss in optical devices, and can be applied to optoelectronics, optical communications, optical sensors and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystal growth, and in particular relates to a fluorocarbonate nonlinear optical crystal and a growth method thereof. Background Art

[0002] Nonlinear optical crystals are one of the important optoelectronic information functional materials. Nonlinear optical crystals can be used for frequency conversion to achieve frequency doubling, frequency combination, frequency difference, optical parametric oscillation, etc. to expand the laser wavelength range. They can also modulate, amplify, switch, store and other processing of optical signals. They have important applications in laser chemistry, laser medicine, laser processing and deep-sea exploration.

[0003] The second-order nonlinear polarizability is the basis for the frequency conversion effect of nonlinear optical crystals. The second-order nonlinear polarizability belongs to the third-order tensor. For centrosymmetric crystals, the second-order nonlinear polarizability is zero and has no frequency doubling effect. Therefore, the most basic property requirement of nonlinear optical crystals is to have a non-centrosymmetric structure.

[0004] Introducing a planar π-conjugated group ([CO3] planar triangular group) into the crystal structure can increase the probability of obtaining non-centrosymmetric crystal materials and effectively improve the optoelectronic properties of the crystal. In addition, the arrangement of the polyhedral ionic groups will affect the nonlinear optical properties of the crystal. When the [CO3] groups are arranged in parallel, polarization is more likely to occur, which is beneficial to improving the birefringence and frequency doubling effect of the crystal.

[0005] Carbonates exist stably in nature. - Ions, CO3 2- The polarizability of ions is large and anisotropic, while F - The ion is weakly isotropic, F - and CO3 2- This polarizability difference between ions may lead to the generation of strong second harmonics in certain structures. K4RE2(CO3)3F4 (Re=Nd, Sm, Eu, Gd) containing carbonate and fluoride ion series has strong frequency doubling performance. Potassium terbium fluorocarbonate K4Tb2(CO3)3F4 provided by the present invention has good nonlinear optical properties. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a fluorocarbonate nonlinear optical crystal and a growth method. To solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0007] A fluorocarbonate nonlinear optical crystal, potassium terbium fluorocarbonate (K4Tb2(CO3)3F4) single crystal, is made of terbium fluoride as raw material and potassium carbonate solution of a certain concentration as mineralizer. It belongs to the trigonal system, has a space group of R32, and a unit cell parameter of α=β=90.0000°, γ=120.0000°;

[0008] Fluorocarbonate materials are easy to decompose at high temperatures, and the preparation methods are mostly co-solvent method or hydrothermal method. However, the decomposition temperature of transition metal carbonates is particularly low, and it is difficult to find a suitable co-solvent. Therefore, the present invention uses a hydrothermal method to synthesize fluorocarbonate. The method for growing potassium terbium fluorocarbonate (K4Tb2(CO3)3F4) single crystals of the present invention comprises the following steps:

[0009] The raw materials of terbium fluoride TbF3 and potassium carbonate K2CO3 mineralizer solution are placed in a gold bushing tube 1 and sealed. Then the gold bushing tube 1 is placed in the autoclave body 2 of the autoclave. Water is added into the interlayer between the gold bushing tube 1 and the autoclave body 2, and the autoclave is sealed. The sealed autoclave is then placed in a resistance furnace 3, and the furnace body temperature is set to 500-650°C. After 2d-14d of constant temperature growth, the cooling rate is set to slowly reduce the temperature to 100°C, and then naturally cooled to room temperature. The autoclave is opened and the gold bushing tube 1 is taken out to obtain potassium terbium fluorocarbonate (K4Tb2(CO3)3F4) single crystal.

[0010] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.

[0011] The crystal of the present invention is a new type of rare earth terbium material coordinated by fluorine and carbonate, has good nonlinear optical properties, can achieve higher transparency and lower optical loss in optical devices, and can be applied to optoelectronics, optical communications, optical sensors and other fields.

[0012] The present invention adopts a subcritical hydrothermal method to grow crystals. Carbonates are easily decomposed at high temperatures. The present invention uses a high-temperature and high-pressure hydrothermal method with a temperature of more than 500°C. The growth temperature is lower than that of a molten salt method. The obtained crystals have high purity, low thermal stress, few macroscopic defects, and can have better crystallization quality and larger crystal size.

[0013] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The accompanying drawings are part of this application and are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0015] Figure 1 It is a schematic diagram of the structure of the equipment used in the crystal growth method of the present invention;

[0016] Figure 2 This is a crystal picture of the present invention;

[0017] Figure 3 It is a refined graph of the XRD powder diffraction data of the crystal of the present invention;

[0018] Figure 4 This is the frequency doubling diagram of the crystal powder of the present invention.

[0019] Figure 5 This is a microscope magnified image of the product of Comparative Example 1;

[0020] Figure 6 This is a microscope magnified image of the product of Comparative Example 2;

[0021] Figure 7 This is the gold lined tube used in Comparative Example 3.

[0022] In the figure: 1. Gold bushing tube; 2. Kettle body; 3. Resistance furnace.

[0023] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0025] Example 1

[0026] The K4Tb2(CO3)3F4 growth method of this embodiment includes the following steps:

[0027] like Figure 1 As shown, 16.2 g of TbF3 and 6M K2CO3 mineralizer solution were placed in the gold bushing tube 1 as hydrothermal reactants, and the filling degree of the hydrothermal reactants was 60%.

[0028] The gold bushing tube 1 is sealed and placed in the autoclave body 2 of the autoclave, and deionized water is added into the interlayer between the gold bushing tube 1 and the autoclave body 2, with the filling degree of deionized water being 45%.

[0029] The autoclave is sealed and placed in a resistance furnace 3. The furnace temperature is set to 600°C. After 7 days of constant temperature growth, the temperature is cooled to 100°C at a rate of 3°C / h. Then, the temperature is naturally cooled to room temperature. The autoclave is opened and the gold bushing 1 is taken out to obtain a K4Tb2(CO3)3F4 single crystal. The crystal picture is shown in FIG. Figure 2 The smaller crystals grown were ground into powder, and the room temperature XRD data of the material were measured and the Rietveld refined spectrum was obtained, such as Figure 3 As shown, the refined residual factor R wp =6.60%, R p =4.59%, GOF=2.47, indicating that the refinement has a good fitting effect, and the obtained K4Tb2(CO3)3F4 sample has high purity and no impurities. The powder frequency spectrum of K4Tb2(CO3)3F4 ( Figure 4 ), as the particle size of K4Tb2(CO3)3F4 gradually increases, the frequency doubling effect also increases, indicating that K4Tb2(CO3)3F4 can achieve phase matching. When the particle size is 109μm-150μm, the powder frequency doubling intensity of K4Tb2(CO3)3F4 is 4.19 times that of KDP.

[0030] Example 2

[0031] The K4Tb2(CO3)3F4 growth method of this embodiment includes the following steps:

[0032] like Figure 1 As shown, 16.2 g of TbF3 and 6M K2CO3 mineralizer solution were placed in the gold bushing tube 1 as hydrothermal reactants, and the filling degree of the hydrothermal reactants was 60%.

[0033] The gold bushing tube 1 is sealed and placed in the autoclave body 2, and deionized water is added to the interlayer between the gold bushing tube 1 and the autoclave body 2, and the filling degree of deionized water is 45%. The autoclave is sealed, and then the sealed autoclave is placed in a resistance furnace 3, and the furnace body temperature is set to 600°C. After 2 days of constant temperature growth, the temperature is lowered to 100°C at a rate of 5°C / h, and then naturally cooled to room temperature, the autoclave is opened, and the gold bushing tube 1 is taken out to obtain a K4Tb2(CO3)3F4 single crystal.

[0034] Example 3

[0035] The K4Tb2(CO3)3F4 growth method of this embodiment includes the following steps:

[0036] like Figure 1 As shown, 16.2 g of TbF3 and 6M K2CO3 mineralizer solution were placed in the gold bushing tube 1 as hydrothermal reactants, and the filling degree of the hydrothermal reactants was 60%.

[0037] The gold bushing tube 1 is sealed and placed in the autoclave body 2, and deionized water is added to the interlayer between the gold bushing tube 1 and the autoclave body 2, and the filling degree of deionized water is 45%. The autoclave is sealed, and then the sealed autoclave is placed in a resistance furnace 3, and the furnace body temperature is set to 600°C. After 2 days of constant temperature growth, the temperature is lowered to 100°C at a rate of 8°C / h, and then naturally cooled to room temperature, the autoclave is opened, and the gold bushing tube 1 is taken out to obtain a K4Tb2(CO3)3F4 single crystal.

[0038] Example 4

[0039] The K4Tb2(CO3)3F4 growth method of this embodiment includes the following steps:

[0040] like Figure 1 As shown, 16.2 g of TbF3 and 6M K2CO3 mineralizer solution were placed in the gold bushing tube 1 as hydrothermal reactants, and the filling degree of the hydrothermal reactants was 60%.

[0041] The gold bushing tube 1 is sealed and placed in the autoclave body 2, and deionized water is added to the interlayer between the gold bushing tube 1 and the autoclave body 2, and the filling degree of deionized water is 45%. The autoclave is sealed, and then the sealed autoclave is placed in a resistance furnace 3, and the furnace body temperature is set to 600°C. After 2 days of constant temperature growth, the temperature is lowered to 100°C at a rate of 10°C / h, and then naturally cooled to room temperature, the autoclave is opened, and the gold bushing tube 1 is taken out to obtain a K4Tb2(CO3)3F4 single crystal.

[0042] Comparative experiment

[0043] Experimental purpose: To prepare K4Tb2(CO3)3F4 crystals.

[0044] Raw materials: TbF3, K2CO3.

[0045] Experimental instruments and equipment: autoclave, gold-lined tube (volume 30 ml), high-temperature furnace.

[0046] Experimental steps:

[0047] 1. Place a certain amount of K2CO3 particles in a beaker and dissolve them to prepare a 1-6M K2CO3 solution;

[0048] 2. Add a certain amount of TbF3 powder into the gold lined tube, then pour in 12-21 ml of K2CO3 solution so that the solution occupies 40-70% of the volume of the gold lined tube (internal filling degree);

[0049] 3. Seal the gold lined tube and place it in an autoclave, and seal the autoclave;

[0050] 4. Place the autoclave in a high-temperature furnace and set the temperature rise and fall program of the high-temperature furnace.

[0051] The experiment conducted four groups of comparisons: Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4.

[0052] Comparative Example 1:

[0053] Conditions: The molar ratio of TbF3 to K2CO3 was 2:1, the programmed cooling rate was 10°C / h, and the internal filling degree was 50%, and the concentration of K2CO3 solution was changed (1, 2, 3, 4, 5, 6M);

[0054] Results: When the concentration was 6 M, the needle-like impurities in the product were the least; Figure 5 The product is at a concentration of 1M.

[0055] Comparative Example 2:

[0056] Conditions: The concentration of K2CO3 solution was 6M, the program cooling rate was 10℃ / h, and the internal filling degree was 50%, and the molar ratio of TbF3 and K2CO3 was changed (1:1, 2:1, 2.5:1, 3:1);

[0057] Results: When the molar ratio of TbF3 to K2CO3 was 2.5:1, the needle-like impurity phase of the product was the least; Figure 6 The product is when the molar ratio is 1:1.

[0058] Comparative Example 3:

[0059] Conditions: The concentration of K2CO3 solution was 6M, the molar ratio of TbF3 and K2CO3 was 2.5:1, and the programmed cooling rate was 10℃ / h. The internal filling degree was changed (40%, 50%, 60%, 70%).

[0060] Results: When the internal filling degree is 60%, the internal and external filling of the gold tube is balanced and the deformation is small ( Figure 7 ), the crystal size of the product is larger.

[0061] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A fluorocarbonate nonlinear optical crystal, characterized in that: Its chemical formula is K4Tb2(CO3)3F4, belonging to the trigonal crystal system, space group is R32, unit cell parameters are a = b = 9.00732 Å, c = 13.62004 Å; α = β = 90.0000°, γ=120.0000°; V = 956.9742 Å 3 ; The hydrothermal method is used, and the specific preparation steps are: Terbium fluoride powder and potassium carbonate mineralizer solution are placed in a gold bushing tube (1) and sealed. The gold bushing tube (1) is then placed in a body (2) of an autoclave. Water is added to the interlayer between the gold bushing tube (1) and the body (2) and the autoclave is sealed. The sealed autoclave is then placed in a resistance furnace (3) and the furnace body temperature is set to 600° C. After 2 days of constant temperature growth, a cooling rate is set to slowly reduce the temperature to 100° C., and then the autoclave is naturally cooled to room temperature. The autoclave is opened and the gold bushing tube (1) is taken out to obtain a potassium terbium fluorocarbonate single crystal.

2. The fluorocarbonate nonlinear optical crystal according to claim 1, characterized in that: The molar ratio of the terbium fluoride powder to potassium carbonate is 1:1 to 3:1, and the potassium carbonate is configured into a 1-6M potassium carbonate mineralizer solution.

3. The fluorocarbonate nonlinear optical crystal according to claim 1, characterized in that: The filling degree of the reactants in the gold-lined tube (1) is 50-70%.

4. The fluorocarbonate nonlinear optical crystal according to claim 1, characterized in that: Deionized water is added into the interlayer between the gold bushing tube (1) and the kettle body (2) with a filling degree of 45%.

5. The fluorocarbonate nonlinear optical crystal according to claim 1, characterized in that: The cooling rate is 3-10℃ / h.